Truth‐Telling and Education‐Making in a Neighborhood in Mexico City. (11th June 2022) - Corson, Jordan
Abstract : This qualitative study examines educational life in a neighborhood in Mexico City, analyzing how discourses have produced the neighborhood, Tepito, as a place "without education." Simultaneously, ethnographic research entangles with theories of radical equality and resistance to explore how education emerges and how certain forms of education circulate throughout the neighborhood. Ultimately, everyday life in Tepito reveals rebellious and playful forms of education that challenge dominant educational discourses and open new understandings of educational possibilities.